Analisis Kesuksesan Penerapan Sistem Informasi pada Sistem Informasi Pelayanan Terpadu (SIPT) Online (Studi Pada PT Jamsostek (PERSERO)) - Purwaningsih, Susanti (Jurnal Ilmu Ekonomi ASET, 2010)
Sistem Informasi Pelayanan Terpadu (SIPT) Online PT Jamsostek (Persero) isan implemented Information System by PT Jamsostek (Persero) to support service for memberof social security program in Indonesia. This research is to test whether system quality,information quality, and service quality positively affect on user satisfaction and to test whethersystem quality, information quality, service quality positively, task-technology fit, and usersatisfaction have positive effect on indvidual impact.. Model used in this research was DeLoneand McLeanâs Information System Success Model (1992), which was modified by addingconstruct of service quality, task-technology fit and eliminating construct of use andorganizational impact of the model. The research was done on employee in PT Jamsostek(Persero) branch offices in Indonesia. Data was obtained by mail survey. 519 questionnairescollected and analysed by using software Smart PLS version 2.0.. The result of test indicatedthat user satisfaction is significantly influenced by system quality, information quality, andservice quality. In addition individual impact due to system use is significantly influenced bysystem quality, information quality, service quality, task-technology fit, and user satisfaction.Keywords : system quality, information quality, service quality, task-technology fit, usersatisfaction individual impact.